ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI FLUIDA STATIS DI SMA KRISTEN EKKLESIA NANGA PINOH - Thira Sona; Stepanus Sahala Sitompul; Erwina Oktavianty (Jurnal Pendidikan : Riset dan Konseptual, 2023)
This research has general objectives and specific objectives. In general, the research objective is to find out whether the students at SMA Kristen Ekklesia Nanga Pinoh already have critical thinking skills. Then there are two specific objectives in this study, namely to describe students' critical thinking skills and to find out the differences in each indicator of participants' critical thinking skills on static fluid material at Ekklesia Nanga Pinoh Christian High School. To achieve the research objectives, a qualitative descriptive method was used. A total of 34 students were used as the sample, the sample selection used a saturated sampling technique. All students who were sampled were students in class XI IPA. The research tool used in this study was a test of critical thinking skills in the form of multiple choice as many as 20 items. The test questions used in this study raised the indicators of critical thinking skills, namely: classification, assessment, inference and strategy which includes static fluid material. The critical thinking skills test results show that students of class XI science at SMA Kristen Ekklesia Nanga Pinoh already have critical thinking skills. with low category. Based on the test results in the study, it showed that each indicator was not much different from one another.